COVID-19 and International Security & Cooperation - Omer Ham Amin Nuradeni (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
It can be said that the emergence of the Covid 19 pandemic, and its rapid spread among all countries of the world, had greatly affected all aspects of the lives of countries within the framework of the international community, and among the aspects affected by the pandemic are aspects of international security and cooperation between the countries of the system Globalism. This is because the concept of security has changed to a very large degree under the influence of the repercussions of the Coronavirus, which has exposed international security and peace to new challenges and risks. Consistent with this, the images and levels of international cooperation to confront the Covid 19 pandemic have undergone a major change, which requires reviewing new formulations of international cooperation in terms of goals and means and crystallizing new forms of them. In general, this scientific research deals with, in addition to its scientific problem and hypothesis, the relationship between change on two levels, namely: the first, the Covid 19 pandemic, and the second, international security and cooperation, by relying on the descriptive-analytical approach, to stand on a comprehensive analytical vision that covers the contents of the research from Its many angles. And he has to deal with the research within its scientific structure, an introduction, and two main topics, the first of which discussed the impact of the Covid 19 pandemic on international security, through two branches, the first of which dealt with the concept of international security in light of the repercussions of the Corona crisis, while the second focused on studying the Covid pandemic 19 as a source of threat to international security. As for the second topic, it was divided into three different branches, which included studying the issue of international cooperation to confront the Corona crisis by discussing the roles of the United Nations General Assembly and the UN Security Council, as well as the World Health Organization. While the research ended to a conclusion, a set of scientific conclusions and recommendations crystallized on it, to provide solutions to the existing research problem in logical and objective ways.